2020
DOI: 10.5578/turkjsurg.4548
|View full text |Cite
|
Sign up to set email alerts
|

Complications and outcomes of 890 living liver donor hepatectomies at a single center: risks of saving loved one’s life

Abstract: Objective: Living liver donor surgery is a major surgical procedure applied to healthy people with mortality and morbidity risks and does not provide any direct therapeutic advantage to the donor. We retrospectively analyzed the postoperative complication of our living liver donors to figure out the risks of donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Second critical outcome was the recovery of liver function (bilirubin and PT/INR peak or value), 9 20 , 23 , 24 , 33 , 44 , 52 , 68 , 71 , 72 , 73 comparative studies and 2 25 , 58 non‐comparative studies were included in the GRADE. The effect from comparative studies was lower with few events.…”
Section: Resultsmentioning
confidence: 99%
“…Second critical outcome was the recovery of liver function (bilirubin and PT/INR peak or value), 9 20 , 23 , 24 , 33 , 44 , 52 , 68 , 71 , 72 , 73 comparative studies and 2 25 , 58 non‐comparative studies were included in the GRADE. The effect from comparative studies was lower with few events.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 939 donors, in 890 donors' followed-up at least 1-year overall early and late complication rate was 19.5%, including 2.9% life-threatening and nearly life-threatening complications. Right donors hepatectomy complication rate (23.3%) was higher than left donor (14.3%) and left lateral sector donor hepatectomy (11.5%) (7). In addition, long-term medical and psychosocial outcomes in living liver donors is always one of the hot topics in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Living liver donor (7) and living kidney donor (8) selection criteria, donor evaluation, surgical techniques and post-operative follow-up plans have been described separately in our previous publications. Donors were both approved by multidisciplinary living liver donor and living kidney donor institutional donor committees.…”
Section: Methodsmentioning
confidence: 99%
“…Majority of the literature states that surgeon and center experience is closely related with lower complication rates [2][3][4][5]. Kim et al reported that the experience of the center was important in order to decrease the complications rates of donor hepatectomy with their series of over 500 donors [3].…”
Section: Discussionmentioning
confidence: 99%
“…Shaji Matthew et al reported 1 mortality due to biliary sepsis [6]. There are other series reporting biliary and overall complications after donor hepatectomy [2][3][4][5][6][7][8][9][10]. A recent systematic review by Braun et al they reviewed 33 studies, reporting outcomes from 12,653 donors (right lobe: 8231, left lobe: 4422) [2].…”
Section: Discussionmentioning
confidence: 99%